DETERMINATION OF REACTION KINETICS USING ONLINE X-RAY DIFFRACTION - Elida Purba (Universitas Gadjah Mada, 2008)
X-ray diffraction (XRD) is a powerful technique for the study of polymorphism and polymorphic phase transformations. Monitoring of phase transformation directly has been very limited to-date. The XRD system used in this study was used to determine the rate of transformation of pure glutamic acid a form to b form in a solution mediated phase. On every run starting from the pure a form, the transformation process was monitored continuously at fixed temperature, and separate experiments were performed as a function of temperature. The operating temperature was varied from 36 to 57 °C with 10% w/w solid concentration. Data were taken every 200 seconds until the transformation was completed. This paper is concerned with a study of the transformation of the alpha (a) form of L-glutamic acid (L-GA) to the beta (b) form in order to determine the kinetic reaction. The rate constant (k), activation energy (Ea) and pre-exponential factor (A) were obtained. Sensitivity tests were also carried out to examine minimum detection limit when both a and b present in the mixture. In addition, effect of particle size on XRD patterns was also determined. The results show that XRD gives useful information to observe polymorphism for pharmaceutical industry.